Genome Sequence of Brevundimonas sp., an Arsenic Resistant Soil Bacterium - Javiera Soto (Diversity, 2021)
Brevundimonas sp. is a bacteria able to grow in metal(loid) contaminated soil from Puchuncaví Valley, central Chile. This study has isolated a bacterial strain capable of growth under high doses of arsenic (As) (6000 mg L−1), and a draft genome sequence was generated. Additionally, real-time PCR was performed to examine the effect of As on some genes related to As resistance. Results demonstrated a total of 3275 predicted annotated genes with several genes related to the ars operon, metal(loid) resistance-related genes, metal efflux pumps, and detoxifying enzymes. Real-time PCR showed that the arsB involved in the efflux of As was down-regulated, whereas arsR, arsH, and ACR3 did not show differences with the addition of As. Our study provides novel evidence of diverse As regulating systems in tolerant bacteria that will lead to a better understanding of how microorganisms overcome toxic elements and colonize As contaminated soils and to the possible use of their specific properties in bioremediation.